PERHITUNGAN VALUE AT RISK MENGGUNAKAN MODEL INTEGRATED GENERALIZED AUTOREGRESSIVE CONDITIONAL HETEROSCEDASTICITY (IGARCH) (Studi Kasus pada Return Kurs Rupiah terhadap Dollar Australia) - Dian Febriana; Tarno Tarno; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Foreign exchange trading can be an alternative investment due to the rapid movement of the exchange rate and its liquid characteristic. Measurement of risk is important because investment is related to substantial funds. One of the popular methods of risk measurement is Value at Risk (VaR) method. In financial time series, data usually have a variance that is not constant (heteroscedastisity). To overcome these problems, ARCH and GARCH models are used. One type of ARCH / GARCH namely Integrated Generalized Autoregressive Conditional Heteroscedasticity (IGARCH). The purpose of this study is modeling the IGARCH volatility and to calculate VaR based on the estimate volatility of the exchange rate return data rupiah against the Australian dollar. This study use daily selling rate data of the rupiah against the Australian dollar from 1 June 2012 until February 28, 2014. The best IGARCH model used for forecasting volatility of exchange rate return data Rupiah against the Australian dollar is the ARIMA model ([10], 0, [19]) IGARCH (1,1) because it has the smallest AIC value. The estimation volatility forecasting results obtained from the IGARCH (1,1) is used to calculate the value at risk on 5 periods ahead with one day holding period and a confidence level of 95%. Value at Risk to be around 0.95% to 1.07% with the highest VaR on 3rd March 2014 and the lowest VaR on 7th March 2014. Keywords : Exchange rate, Volatility, Integrated Generalized Autoregressive Conditional Heteroscedasticity (IGARCH), Value at Risk (VaR)